Dampak Perubahan Iklim Terhadap Ekosistem Pesisir Dipantai Pangandaran - Nurul Nitami Ahmady; Ishaq Rahman (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Climate change poses a significant global challenge that impacts coastal ecosystems in various parts of the world, including Pangandaran Beach, Indonesia. This study aims to identify the effects of climate change, such as rising sea temperatures, increasing sea levels, and changing rainfall patterns, on biodiversity and the sustainability of coastal ecosystems in the region. The methods employed include climate data analysis, field observations, and interviews with local communities and stakeholders. Findings indicate that the coral reef ecosystems at Pangandaran Beach are experiencing declining health due to coral bleaching, while fish populations are decreasing as habitats diminish. Additionally, the increasing frequency and intensity of storms exacerbate coastal erosion and threaten the livelihoods of fishing communities. These findings underscore the urgent need for sustainable mitigation and adaptation strategies to protect coastal ecosystems and enhance the resilience of local communities against the impacts of climate change.